Temporal variability of microbial response to crude oil exposure in the northern Gulf of Mexico - Brock, Melissa L.; Richardson, Rachel; Ederington-Hagy, Melissa; Nigro, Lisa; Snyder, Richard A.; Jeffrey, Wade H. (Frontiers in Ecology and Evolution, 2023)
Oil spills are common occurrences in the United States and can result in extensive ecological damage. The 2010 Deepwater Horizon oil spill in the Gulf of Mexico was the largest accidental spill recorded. Many studies were performed in deep water habitats to understand the microbial response to the released crude oil. However, much less is known about how planktonic coastal communities respond to oil spills and whether that response might vary over the course of the year. Understanding this temporal variability would lend additional insight into how coastal Florida habitats may have responded to the Deepwater Horizon oil spill. To assess this, the temporal response of planktonic coastal microbial communities to acute crude oil exposure was examined from September 2015 to September 2016 using seawater samples collected from Pensacola Beach, Florida, at two-week intervals. A standard oil exposure protocol was performed using water accommodated fractions made from MC252 surrogate oil under photo-oxidizing conditions. Dose response curves for bacterial production and primary production were constructed from 3H-leucine incorporation and 14C-bicarbonate fixation, respectively. To assess drivers of temporal patterns in inhibition, a suite of biological and environmental parameters was measured including bacterial counts, chlorophyll a, temperature, salinity, and nutrients. Additionally, 16S rRNA sequencing was performed on unamended seawater to determine if temporal variation in the in-situ bacterial community contributed to differences in inhibition. We observed that there is temporal variation in the inhibition of primary and bacterial production due to acute crude oil exposure. We also identified significant relationships of inhibition with environmental and biological parameters that quantitatively demonstrated that exposure to water-soluble crude oil constituents was most detrimental to planktonic microbial communities when temperature was high, when there were low inputs of Total Kjeldahl Nitrogen, and when there was low bacterial diversity or low phytoplankton biomass.